The Latest Battles Between EGFR Monoclonal Antibodies and Resistant Tumor Cells - Cai, Wen-Qi; Zeng, Li-Si; Wang, Li-Feng; Wang, Ying-Ying; Cheng, Jun-Ting; Zhang, Ying; Han, Zi-Wen; Zhou, Yang; Huang, Shao-Li; Wang, Xian-Wang; Peng, Xiao-Chun; Xiang, Ying; et al. (Frontiers in Oncology, 2020)
Epidermal growth factor receptor (EGFR) is a tyrosine kinase receptor involved in homeostatic regulation of normal cells and carcinogenesis of epithelial malignancies. With rapid development of the precision medicine era, a series of new therapies targeting EGFR are underway. Four EGFR monoclonal antibody drugs (cetuximab, panitumumab, nimotuzumab, and necitumumab) are already on the market, and a dozen other EGFR monoclonal antibodies are in clinical trials. Here, we comprehensively review the newly identified biological properties and anti-tumor mechanisms of EGFR monoclonal antibodies. We summarize recently completed and ongoing clinical trials of the classic and new EGFR monoclonal antibodies. More importantly, according to our new standard, we re-classify the complex evolving tumor cell resistance mechanisms, including those involving exosomes, non-coding RNA and the tumor microenvironment, against EGFR monoclonal antibodies. Finally, we analyzed the limitations of EGFR monoclonal antibody therapy, and discussed the current strategies overcoming EGFR related drug resistance. This review will help us better understand the latest battles between EGFR monoclonal antibodies and resistant tumor cells, and the future directions to develop anti-tumor EGFR monoclonal antibodies with durable effects.